Pengaruh Literasi Keuangan, Locus Of Control dan Financial Technology Terhadap Perilaku Pengelolaan Keuangan Individu - Eugenianda, Alfarizqi Nur; Safitri, Maria (Faculty of Economics and Business Universitas Dian Nuswantoro, 2024)
Financial Management Behavior is an activity carried out by individuals in compiling, organizing and managing their finances. This study aims to determine the influence of financial literacy, locus of control, and financial technology on individual financial management behavior. The type of research used in this study is quantitative research and data analysis techniques using Structural Equation Modeling (SEM) analysis with SmartPLS 3.0 software. The total population obtained was 527 management students of Dian Nuswantoro University in 2020. The number of samples obtained was 172 respondents using purposive sampling techniques and taken from an online questionnaire in the form of a google form. The results of the study concluded that financial literacy and locus of control have a positive and significant influence on financial management behavior. However, financial technology does not affect financial management behavior.Perilaku Pengelolaan Keuangan adalah kegiatan yang dilakukan oleh individu dalam menyusun, mengatur dan mengelola keuangan yang dimiliki. Penelitian ini bertujuan untuk mengetahui pengaruh literasi keuangan, locus of control, dan financial technology terhadap perilaku pengelolaan keuangan individu. Jenis penelitian yang digunakan dalam penelitian ini adalah penelitian kuantitatif serta teknik analisis data menggunakan analisis Structural Equation Modelling (SEM) dengan software SmartPLS 3.0. Jumlah populasi yang diperoleh sebesar 527 mahasiswa manajemen universitas dian nuswantoro tahun 2020. Jumlah sampel yang diperoleh sebanyak 172 responden dengan menggunakan teknik purposive sampling serta diambil dari kuesioner online berupa google form. Hasil riset menyimpulkan bahwa literasi keuangan dan locus of control memberikan pengaruh positif dan signifikan terhadap perilaku pengelolaan keuangan. Akan tetapi, financial technology tidak memberi pengaruh terhadap perilaku pengelolaan keuangan.Keywords:Literasi KeuanganLocus of ControlFinancial TechnologyPerilaku Pengelolaan Keuangan